The link between negative affect, vagal tone, and visceral sensitivity in quiescent Crohn's disease. Issue 8 (25th May 2014) - Rubio, A.; Pellissier, S.; Picot, A.; Dantzer, C.; Bonaz, B.
Abstract Autonomic dysfunction and mood disorders are frequently described in Crohn's disease (CD) and are known to influence visceral sensitivity. We addressed the link between vagal tone, negative affect, and visceral sensitivity in CD patients without concomitant features of irritable bowel syndrome (IBS). Rectal distensions to a discomfort threshold of 70% and onset of pain were performed in nine CD patients in remission and eight healthy controls. Autonomic parameters were evaluated with heart rate variability and electrodermal reactivity. We showed that CD patients had (i) higher scores of depressive symptomatology (12 ± 3 in patients vs 4 ± 1 in controls on the Center for Epidemiologic Studies‐Depression Scale; p = 0.038), (ii) reduced vagal tone (HF 257 ± 84 ms2vs 1607 ± 1032 ms2, p = 0.043; LF 455 ± 153 ms2vs 1629 ± 585 ms2, p = 0.047), (iii) decreased sympathetic reactivity during an aversive stimulus, and (iv) higher tolerance to rectal distension pressures (43 ± 3 mmHg vs 30 ± 2 mmHg, p = 0.002) and low sensitivity index scores. In conclusion, our results provide preliminary evidence that patients with quiescent CD, in the absence of IBS, are hyposensate to experimental rectal distension. These data provide further evidence that anxiety and depressive symptomatology in addition to autonomic dysfunction modulate visceral pain perception in quiescent CD patients in the absence of IBS.